WGS and WTS in leukaemia: A tool for diagnostics?. Issue 3 (September 2020) - Meggendorfer, Manja; Walter, Wencke; Haferlach, Torsten
Abstract: The diagnosis of haematological malignancies requires a plethora of methods to evaluate primarily the morphology, but also immunophenotypic and genetic markers. However, intratumoural and interpatient tumour heterogeneity present a challenge when it comes to achieve early diagnosis and informed treatment decisions. Here, the clinical potential of personalized genome and transcriptome sequencing as a comprehensive diagnostic approach is just beginning to be realized, whereas the analysis and clinical interpretation of the acquired data requires a solid knowledge base and sophisticated bioinformatics workflows. Personalized sequencing is already clinically applied and offers the possibility to refine molecular diagnostics, to more accurately assess disease risk and to optimize and personalize treatment decisions. This article reflects the current status of whole genome and transcriptome sequencing as a diagnostic tool for haematological neoplasms, describes pre-analytical and analytical considerations and discusses the current challenges and limitations of the approach.